Women under the Bō tree: Buddhist nuns in Sri Lanka - Bartholomeusz, Tessa J. (Cambridge studies in religious traditions, 1994)
Women under the Bo Tree examines the tradition of female world-renunciation in Buddhist Sri Lanka. The study is textual, historical and anthropological, and links ancient tradition with contemporary practice. Tessa Bartholomeusz utilizes data based on her field experiences in many contemporary cloisters of Sri Lanka, and on original archival research. She explores the history of the re-emergence of Buddhist female renouncers in the late nineteenth century after a hiatus of several hundred years; the reasons why women renounce; the variety of expressions of female world-renunciation; and, above all, attitudes about women and monasticism that have either prohibited women from renouncing or have encouraged them to do so. One of the most striking discoveries of the study is that the fortunes of Buddhist female renouncers is tied to the fortunes of Buddhism in Sri Lanka more generally, and to perceived notions of Sri Lanka as the caretaker of Buddhism.